Intelligent Pest Manager and Identification of Leaf Disease - N Kethana Sai, K Suhit, K Balaji, N Preetham (International Journal of Advanced Science and Technology, 2020)
Agriculture is the important sources for the survival of both humans and animals. New technologies are used for improving the better productivity of crops. Researchers have developed monitoring and automation system for various techniques of farming. To get high profit in agriculture, crops should be monitored by IOT enabled devices. From this large amount of  unstructured data will be generated in. In the proposed system, Image processing techniques are used to identify the disease of the leaf which in turn used to identify the disease of the crop and growth of the crops. Using CNN algorithm the image of the leaf is classified. Based on the prediction, the kind of pesticides required for fields are identified. This information will be notified to farmers. So that the diseased plant can be removed from the crop rather than using pesticides for the whole crop. The farmers can easily take decisions  from historical data with agricultural analysis to get high productivity.